สนามวาทกรรม "ความผิดเพศ" และความเกลียดชังทางเพศวิถีที่มีต่อกลุ่มเกย์เพศชายกลุ่มต่างๆภายใต้บริบท "สังคมนิยมชาย" ในประเทศไทย ในศตวรรษที่ 21 - ธนา ร่างน้อย (จุฬาลงกรณ์มหาวิทยาลัย, 2023)
This research study has the objectives and arguments to study and analyze the formation of the "Sexual Disorder Discursive Field" within the context of "Patriarchy" in Thai which focus on the practice of that  discursive field in the 21st century between the heterosexual discourse and the homosexual discourse to analyze the relationship and occurrence of sexual hatred towards gay males in Thai society by analysis of various forms of social media and popular culture such as drama series, movies, songs or books, as well as symbolic expressions like Pride Festival and analysis of a set of official discourses such as "law" : the draft bill to amend the Civil and Commercial Code for equal marriage. and the Draft Civil Partnership Act that still has problems with the access to justice and limited of rights and freedoms. It reflects the struggle for rhetorical space in the discursive field that leads to sexual hatred towards the gay group. The study found that Gay male in Thai society still affected by that discursive field especially regarding the protection of rights and freedoms and access to legal rights and the lack of laws that support and access to rights of sexual diversity groups which leading to sexual hatred towards the gay males. Finally, this research has made academic contributions about discourse studies and discourse analysis and create knowledge about gender diversity as well as creating a clearer understanding of criminology regarding sexual hatred towards gay male.